Metamorphic evolutions of high-pressure low-temperature units from ophiolitic mélange of North Soghan (NE Hajiabad, Hormozgan) - akbar ahmadvand; Mohsen Nasrabady; Abbas Asiabanha; Kazem Gholizadeh (پترولوژی, 2021)
The Seghin metamorphic complex of ophiolitic mélange from the north Soghan, composed of metamorphic suites varying in protolith and metamorphic grade. The rock units of this complex have been metamorphosed under PT conditions of pumpellyite- actinolite, greenschist- Ep amphibolite and blueschist facies enclosed by a serpentinitic mélange. The pumpellyite- actinolite and greenschist- Ep amphibolite facies rocks display overprinted metamorphic evidences of blueschist facies as glaucophane overgrowth around actinolite and magnesiohornblende crystals. The average temperature and pressure calculated by thermocalc software and petrogenetic grids is 6- 7, 290- 350 and 11 Kb, 350 ˚C for pumpellyite- actinolite schist and blueschist samples, respectively. The relations of minerals transformation, thermobarometry calculations and the lawsonite preservation are in accordance with counter- clockwise metamorphic path. Generally, the metamorphic blocks of serpentinitic mélange with counter- clockwise PT path like Seghin complex are characteristics of long- lived subduction systems. During the onset of subduction event and attaining to blueschis facies, metamorphic path of down- going slab has passed through greenschist- Ep amphibolite facies. Then, the prograde metamorphic path extending across Pmp- Act subfacies owing to decreasing of geothermal gradient during maturity of subduction setting. Consequently, hairpin- like PT path is governed that is characteristic of Franciscan- type accretionary prisms.